Stem cells as therapeutical option for the treatment of bronchopulmonary dysplasia - Dominik Monz; Erol Tutdibi; Ludwig Gortner (Hygeia Press di Corridori Marinella, 2015)
During the past decades clinical results in neonatology have improved dramatically and increased the survival rate of preterm infants significantly. However, the short and long term outcome of these high-risk preterm infants is mainly influenced by respiratory diseases and neurological damages. Despite great advances in perinatal medicine, there is still no satisfactory treatment for bronchopulmonary dysplasia (BPD) and current approaches are only supportive, have strong adverse effects or only show small benefits. Stem cell based therapies as well as other modes of regenerative strategies are applied as standard therapy in childhood predominantly in paediatric oncology. To date, such therapies have successfully been applied to treat immunodeficiency disorders and aplastic anaemia. But regenerative medicine might be an option for the treatment of BPD in preterm infants. According to some first preclinical results stem cell administration appears as a promising tool to improve the clinical outcome in high-risk infants. For severe neonatal diseases, e.g. hypoxic-ischemic encephalopathy (HIE) in term neonates or BPD in preterm infants, a number of animal models have been established. Although these studies showed positive effects of stem cells in animal models of BPD several questions still remain. Further studies with appropriate preclinical neonate models and carefully controlled clinical trials are needed to assess the significance of regenerative therapies. In this review, we summarize recent results of some experimental and clinical studies that used stem cells to treat BPD associated with impairment of lung development.   Proceedings of the 2nd International Course on Perinatal Pathology (part of the 11th International Workshop on Neonatology · October 26th-31st, 2015) · Cagliari (Italy) · October 31st, 2015 · Stem cells: present and future Guest Editors: Gavino Faa, Vassilios Fanos, Antonio Giordano